Critical Evaluation of The Book of At-Tashrif and Al-Amtsilah At-Tashrifiyyah: A Comparative Study of Sharaf Textbooks in Islamic Boarding Schools - Agus Rohman; Dede Mulyanto; Epon Sopiah; Muhammad Irfan (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study evaluates the quality and relevance of two popular Arabic grammar textbooks commonly used in Islamic boarding schools (pesantren): Kitab at-Tashrif and Al-Amtsilah at-Tashrifiyyah. These textbooks have long served as key references in teaching sharaf (Arabic morphology) in pesantren, yet there has been no comprehensive research comparing the two. Given the evolving times and increasingly dynamic needs of Arabic language education, this study is important. A qualitative approach was employed using document analysis as the research method. The data from the two textbooks were analyzed in depth based on a relevant theoretical framework for textbook evaluation. The aspects analyzed included book structure, language, content, teaching methods, exercises, and assessments. The findings indicate that both textbooks have their strengths and weaknesses. Kitab at-Tashrif generally offers a more systematic structure and clearer presentation of material but lacks variety in exercises and assessments. On the other hand, Al-Amtsilah at-Tashrifiyyah is rich in examples but provides less in-depth explanations of concepts. Both textbooks also did not accommodate contemporary developments and the needs of modern pesantren students, particularly in terms of cultural content and teaching methodology. Based on the findings, it can be concluded that both textbooks still need improvement to meet modern textbook standards. Recommendations include developing more contextual materials, adding a greater variety of exercises and assessments, and integrating technology into the learning process. However, this study has limitations, as it only analyzes two specific textbooks and does not involve direct participation from teachers or students. Further research could involve a larger pool of participants and employ more diverse research methods to obtain more comprehensive results.